PENYULUHAN PEMANFAATAN LAHAN PEKARANGAN DENGAN TANAMAN DAUN BAWANG PADA MASYARAKAT DI DESA SUNGAI BESAR KECAMATAN KARANG INTAN KABUPATEN BANJAR - Ahmad Baparki; Bahrun (INSPIRASI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The utilization of yard land will provide benefits for family life such as: a source of spring onions and also as a source of income. The yard is an open area located around the house. Utilization of yard land will provide benefits for family life such as a source of spring onions. A large yard will be more flexible for planting. If you have a large yard, the methods that can be done include planting directly in the ground (beds), can be combined with using pots, polybags, and vertical culture. However, in a narrow yard, what can be done is planting with planting media such as pots, polybags and vertical culture and agricultural technology that can be applied to utilize yard land with hydroponic technology. The utilization of home yard land in the community in Sungai Besar Village, Karang Intan District, Banjar Regency is one of the places that can be utilized by the community for various activitie